One Size Does Not Fit All: A Multifaceted Approach to Educate Families about Newborn Screening - Marianna H. Raia; Molly M. Lynch; Alyson C. Ward; Jill A. Brown; Natasha F. Bonhomme; Vicki L. Hunting (MDPI AG, 2024)
All families deserve access to readily available, accurate, and relevant information to help them navigate the newborn screening system. Current practices, limited resources, and a siloed newborn screening system create numerous challenges for both providers and families to implement educational opportunities to engage families in ways that meet their needs with relevant and meaningful approaches. Engaging families in newborn screening, especially those from historically underserved communities, is necessary to increase knowledge and confidence which leads to overall improved outcomes for families. This article describes three strategies that the Navigate Newborn Screening Program developed, tested, and implemented in the United States, including online learning modules, a prenatal education pilot program, and social media awareness campaign, as well as the extent to which they were successful in reaching and educating families about newborn screening. Using quality improvement methods and evidence-driven approaches, each of these three strategies demonstrate promising practices for advancing awareness, knowledge, and self-efficacy for families navigating the newborn screening system-particularly families in medically underserved and underrepresented communities. A model for bidirectional engagement of families is outlined to support scaling and implementing promising educational efforts for both providers and families in the newborn screening system.